1998
DOI: 10.1103/physrevlett.81.1310
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Laser Induced Conductive and Resistive Transients inLa0.7Ca0.3MnO3

Abstract: Pulsed laser excitation induced conductance changes in colossal magnetoresistance material La 0.7 Ca 0.3 MnO 3 were studied on the picosecond time scale. A two-component signal was seen consisting of a fast positive transient associated with the paramagnetic insulating state and a slower negative signal associated with the ferromagnetic metallic state. The fast component corresponds to the photoionization of the Jahn-Teller small polaron. The slow component is explained in terms of the reduced carrier mobility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 18 publications
1
30
0
1
Order By: Relevance
“…19 The higher energy band at 652.6 nm is attributed to the transition, determined by the crystal field energy E C , between a t 2g core electron of Mn 3+ to the spin-up e g bands of Mn 4+ by a dipole allowed charge transfer process, the 700.5 nm band is assigned to the transition between the spin-up and spin-down e g bands separated by the Hund's coupling energy E J , while the 789.8 nm band is identified as the charge transfer excitation band of an electron from the lower J-T split e g level of a Mn 3+ ion to the e g level of an adjacent Mn 4+ ion. A basic electronic structure of the e g and t 2g levels of Mn 3+ and Mn 4+ as proposed by Zhao et al 24 from a pulsed laser excitation induced conductance in bulk La 0 7 Ca 0 3 MnO 3 is followed. Evidently, a markedly modified emission arises with e-p coupling in single domain La 0 67 Ca 0 33 MnO 3 nanoplates as follows.…”
Section: Methodsmentioning
confidence: 99%
“…19 The higher energy band at 652.6 nm is attributed to the transition, determined by the crystal field energy E C , between a t 2g core electron of Mn 3+ to the spin-up e g bands of Mn 4+ by a dipole allowed charge transfer process, the 700.5 nm band is assigned to the transition between the spin-up and spin-down e g bands separated by the Hund's coupling energy E J , while the 789.8 nm band is identified as the charge transfer excitation band of an electron from the lower J-T split e g level of a Mn 3+ ion to the e g level of an adjacent Mn 4+ ion. A basic electronic structure of the e g and t 2g levels of Mn 3+ and Mn 4+ as proposed by Zhao et al 24 from a pulsed laser excitation induced conductance in bulk La 0 7 Ca 0 3 MnO 3 is followed. Evidently, a markedly modified emission arises with e-p coupling in single domain La 0 67 Ca 0 33 MnO 3 nanoplates as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Take the kinetic/ dynamic behavior of the charge carriers as an example. 12,13 When the diffusion distance of the photocarriers is comparable or smaller than film thickness, size effect may occur, resulting in dramatic changes in the photovoltaic properties of the junctions. As we know, the injection, drift and diffusion of charge carriers are important topics of electronics.…”
Section: Influence Of Film Thickness On the Physical Properties Of Mamentioning
confidence: 99%
“…The study of the picosecond magnetization dynamics of manganites was reported by Zhao et al, 13 who monitored the optically induced conductance changes in LCMO films with 20-ps time resolution. Long-lived spin excitations were found responsible for a resistivity increase in the ferromagnetic phase.…”
Section: Introductionmentioning
confidence: 99%